Biological aspects of Longfin Mojarra (Pentaprion longimanus, Cantor 1849) in north coast of Central Java, Indonesia - DIAN OKTAVIANI; RIA FAIZAH; DUTO NUGROHO (Biodiversitas Journal of Biological Diversity, 2018)
Oktaviani D, Faizah R, Nugroho D. 2018. Biological aspects of Longfin Mojarra (Pentaprion longimanus, Cantor 1849) in north coast of Central Java, Indonesia. Biodiversitas 19: 683-689. Longfin Mojarra (Pentaprion longimanus) locally named as rengganis, is a demersal fish species that is commonly caught in Scottish seine fisheries off the north coast of Java. The fisheries are in heavily harvest level since decades. The aim of this study was to observe the biological aspects of this species. Observations were made between August 2014-July 2015 from Tegal fishing port, western part of north coast central Java. General life-history parameters were measured, i.e., monthly length frequency for 1876 fishes, among them 573 specimens were observed for length-weight relationship, including 541 specimens for sex ratio and maturity stages. Fulton index, Gonadosomatic index, sex ratio and estimated length at first mature were analyzed. The result showed fish size ranged between 7.4 to 15.3 cmFL with the average length of 11.2+1.75 cmFL. We found that length-weight relationship tends to be isometric which statistically the body growth coefficient (b) is equal to 3 (tc = 0.53 < tab; p<0.05) . Monthly Fulton indexes ranged between 1.05-2.87 with an average of 1.90 + 0.17. Sex ratio during observation was not significantly different (p<0.05) from the expected ratio of 1: 1. Mature females occurred year-round with the highest percentage observed from January to April 2015. The estimated length at first maturity was 13.04 cm FL. These biological parameters will be used to support the population study of the future demersal fish species to improve conservation and management measures.